The role of administrative empowerment in easing the pressures of work - مخلوف سعاد; عيواج صونيا (International Journal of Social Communication, 2020)
Managing work stress is one of the important topics in the field of psychology, work and organization in general and organizational behavior in particular, because of its effective and significant role in identifying directions for empowering human resources in organizations, as the latter (empowering human resources) is the core of the administrative creativity of any organization Admin. Therefore, two variables (administrative empowerment, work pressure) interacted to form the intellectual framework for this study, which is the role of administrative empowerment in reducing work pressure. This study aims to know the role of administrative empowerment in reducing work pressure, as well as identifying the level of work pressure among the study sample, and the descriptive approach was used in this study due to the nature of the information collected and the type of study, and the questionnaire was used as an ideal tool for data collection for our study. We applied this questionnaire to a sample of 30 employees, who were chosen in a stratified random manner. The mean and standard deviation were calculated and the study found: Administrative empowerment has a minimal role in alleviating employee stress. Average level of work pressure for employees